A brief review of diagnostic properties of point-of-care ultrasound for adult bowel intussusception: Making the case for ultrasound - Tempel David G.; Balk Daniel S.; Schafer Jesse M.; Hoffmann Beatrice (Journal of Ultrasonography, 2023)
Undifferentiated abdominal pain in adults is a common chief complaint in acute care clinics and emergency departments worldwide, representing up to 10% of visits to emergency departments. Many patients have a non-specific presentation and an initial workup with labwork, urine analysis or X-ray might not reveal a specific diagnosis. Although bowel intussusception is a primarily pediatric disease, adult intussusception is a recognized but rare cause of bowel obstruction often requiring surgical intervention. However, recent data from advanced multi-detector computed tomography imaging shows that milder or recurring cases in adults have been underrecognized. Multi-detector computed tomography is still the imaging gold standard for detecting intussusception in adults, but new data showed that sonographers with basic training using the point-of-care ultrasound approach have a reasonable accuracy in detecting this pathology. As the point-of-care ultrasound for undifferentiated abdominal pain is an emerging core skill in the acute care setting, knowledge of sonographic signs of intestinal intussusception should be included in the skill set of physicians. Sonographic findings in adults mimic pediatric cases, but different location patterns and higher malignancy rates exist in adults. In this manuscript, we will review the current literature on adult intussusception and summarize key knowledge of intestinal intussusception in adults. We will present four adult patients diagnosed with different types of adult acute bowel intussusception using the point-of-care ultrasound and describe a focused scanning approach with typical sonographic findings.